2021
DOI: 10.14256/jce.3195.2021
|View full text |Cite
|
Sign up to set email alerts
|

Structural renovation of residential building in Zagreb after the 22 March 2020 earthquake

Abstract: The phases that must be completed so that a building damaged in earthquake that struck Zagreb on 22 March 2020 can be renovated and strengthened to the required level of seismic resistance are presented in the paper. All phases are therefore presented, starting from the rapid and then detailed inspection, and continuing with preparation of the structural condition assessment report, preparation of renovation design and, finally, ending with realisation of work with expert supervision. A special attention is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…The masonry properties used are based on investigative post-earthquake assessments on similar buildings [48,49,63,64] and are shown in Table 2. Linear static analysis of the structure was carried out, and it was concluded that all walls meet the load-bearing conditions and the geometric conditions.…”
Section: Modelling and Design Of Seismic Strengthening Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The masonry properties used are based on investigative post-earthquake assessments on similar buildings [48,49,63,64] and are shown in Table 2. Linear static analysis of the structure was carried out, and it was concluded that all walls meet the load-bearing conditions and the geometric conditions.…”
Section: Modelling and Design Of Seismic Strengthening Methodsmentioning
confidence: 99%
“…Following the rapid post-earthquake assessment, the building was assigned the N2 label-not usable due to damage, which means that the structure has reached its loadbearing capacity, and there is a possibility of a collapse of load-bearing and non-loadbearing elements. For a full description of the post-earthquake procedures and damage grading the reader is addressed to [47][48][49][50].…”
Section: Post-earthquake Damage Assessmentmentioning
confidence: 99%
“…S obzirom da se analitički pristup temelji na simulaciji potresnih pobuda, konstrukciju je potrebno adekvatno modelirati i opteretiti (Slika 5). Postoje brojni primjeri modeliranja zidanih konstrukcija nakon potresa, a u posljednje vrijeme objavljeno je i nekoliko studija slučaja relevantnih za Hrvatsku, odnosno studija slučaja nakon zagrebačkog potresa [19][20][21][22][23][24].…”
Section: Analitički Pristupunclassified